2020
DOI: 10.3390/medicina56010026
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Albumin and Severity of Pulmonary Embolism

Abstract: Background and Objectives: Inflammation is considered a risk factor for venous thromboembolism. The association between inflammatory markers and the severity of acute pulmonary embolism (APE) has not been explored. Methods: We studied the association between two crude markers of inflammation, serum albumin, and red cell distribution width (RDW) and massive versus non-massive APE. Results: Among 552 consecutive cases of CT-angiogram-confirmed APE, a total of 46 cases (8.3%) had massive APE. Despite similar demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
(31 reference statements)
2
22
0
1
Order By: Relevance
“… 11 Studies have found that low albumin level disrupts physiological functions of albumin, and it increases susceptibility to tromboembolic events, such as deep venous thrombosis and stroke. 12 - 14 Hypoalbuminemi was found to be an independent predictor of mortality in acute PE due to its’ prothrombotic effects, which supports our finding. 11 , 15 , 16 In our study, the value of AUC was statistically significant ( P < 0.001) for cut-off value of albumin <3.17 to predict 30 day mortality in intermediate-high risk acute PE.…”
Section: Discussionsupporting
confidence: 82%
“… 11 Studies have found that low albumin level disrupts physiological functions of albumin, and it increases susceptibility to tromboembolic events, such as deep venous thrombosis and stroke. 12 - 14 Hypoalbuminemi was found to be an independent predictor of mortality in acute PE due to its’ prothrombotic effects, which supports our finding. 11 , 15 , 16 In our study, the value of AUC was statistically significant ( P < 0.001) for cut-off value of albumin <3.17 to predict 30 day mortality in intermediate-high risk acute PE.…”
Section: Discussionsupporting
confidence: 82%
“…In a study from USA with 15300 people, authors reported increased rates of thromboembolism in cases with hypoalbuminemia (5) . Similarly, in a study on 552 patients with PTE hypoalbuminemia was found to be associated with severity of PTE (15) . There are several reasons for this association.…”
Section: Discussionmentioning
confidence: 80%
“…There is no cellular infiltration in the pulmonary artery during the acute stage while leukocyte infiltration occurs within the subsequent three hours and two days, which decreases on the fourth day and returns to baseline levels on the eighth day (18). Inflammatory markers including WBC, HB, NE, LY, PLT, RDW, and MPV, which are inexpensive and standard biomarkers that are routinely measured in CBC, have recently become a major research area in the evaluation of PTE (21,22). In those studies, serum levels of these markers have been shown to decrease or increase in PTE.…”
Section: Resultsmentioning
confidence: 99%